Analisis Implementasi Standar Pelayanan Administrasi di KUA Kecamatan Tamalate Kota Makassar - Najma, Muh.; Faqih M, Ahmad; Arib, Muh.; Raihan M, Ahmad; Aditya, Andi Febrian; A, Asni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study analyzes the implementation of administrative service standards at the Office of Religious Affairs (KUA) in Tamalate District, Makassar City. Using a qualitative method with a descriptive approach, data was obtained through observation, interviews, and documentation. The results of the study indicate that administrative services at the KUA have referred to applicable regulations, but there are still several obstacles, such as limited staff, lack of facilities, and minimal socialization to the community. However, improvement efforts have been made, including the use of digital technology in several services. Public satisfaction with the service is quite good, but there are still complaints regarding and lack of clear information. To improve the quality of service, it is necessary to increase the number of employees, optimize the digital system, and improve facilities and infrastructure. This study is expected to be an evaluation material for the KUA in improving administrative service standards that are more transparent, efficient, and responsive to community needs.